Gel plugging agent containing organic silicon cross-linking agent and nano aluminum oxide and preparation method of gel plugging agent

By introducing silicone crosslinking agent and nano alumina into the drilling fluid, the composition and preparation methods of gel leak plugging agent are optimized, and the performance limitations of traditional leak plugging agents in high temperature and high pressure environments are solved, and better plugging is achieved Leakage effect and stability, suitable for high-temperature deep crack leakage formations.

CN119193117AInactive Publication Date: 2024-12-27YANCHANG OIL FIELD +1
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411313838.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-20
Publication Date
2024-12-27
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

Traditional drilling fluid leak plugging agents show performance limitations under high temperature and high pressure and complex geological conditions. Conventional organometallic crosslinking agents are easy to decompose, and fillers and tougheners have limited effects in improving the strength and toughness of the leak plugging agent, making it difficult to be effective. Solve the problem of deep crack leakage in high temperatures.

Method used

Using gel leak plugging agent containing silicone crosslinking agent and nano alumina, the mechanical strength, thermal stability and overall performance of the leak plugging agent are improved by optimizing the component ratio and preparation method, and delaying the crosslinking effect, which is suitable for high temperature and high pressure Leakage plugging needs in the environment.

Benefits of technology

It achieves better leakage plugging effect in high-temperature deep crack leakage formations, improves the safety and economy of oil and gas field development, and the high specific surface area of ​​nano alumina and the chemical stability of silicone crosslinking agents have significantly improved leakage plugging performance of agent.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005051537760000091
    Figure BDA0005051537760000091
Patent Text Reader

Abstract

The invention provides a gel plugging agent containing an organic silicon cross-linking agent and nano aluminum oxide and a preparation method of the gel plugging agent, belongs to the technical field of drilling fluid plugging, and is used for solving the problem of shaft leakage in oil-gas field development. The plugging agent is prepared from partially hydrolyzed polyacrylamide, chitosan, sodium tripolyphosphate, an organic silicon cross-linking agent, a dispersing agent, a toughening agent, nano aluminum oxide and water, and has high mechanical strength, heat stability and good expansion performance. The preparation method comprises the following steps: dispersing the flexibilizer and the nano aluminum oxide in water, adding other components, and uniformly mixing. The plugging agent can effectively plug high-temperature deep cracks and delay crosslinking to ensure gelling at the positions of the deep cracks, and is simple to prepare and small in environmental pollution. The effectiveness and the practicability of the method are verified by specific embodiments, and the method has important industrial application value and market prospect.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of drilling fluid plugging, and in particular to a gel plugging agent containing an organosilicon cross-linking agent and nano-alumina and a preparation method thereof. Background Art

[0002] In the process of oil and gas field development, wellbore leakage is a common and serious problem. Leakage not only leads to waste of drilling fluid and completion fluid, but also affects the stability of the wellbore and even leads to safety accidents such as blowouts. In order to effectively solve the problem of wellbore leakage, a variety of plugging agents have been developed on the market. Gel plugging agents have been widely used due to their excellent physical and chemical properties and good plugging effect.

[0003] Traditional gel plugging agents are mainly composed of partially hydrolyzed polyacrylamide (HPAM), chitosan, cross-linking agents and other ingredients. These plugging agents can meet the plugging needs of wellbore leakage to a certain extent, but the performance of traditional plugging agents still has certain limitations when facing high temperature, high pressure and complex geological conditions. For example, conventional organic metal cross-linking agents are easy to decompose in high temperature environments, affecting the plugging effect, and some traditional fillers and toughening agents have limited effects in improving the strength and toughness of plugging agents.

[0004] In recent years, nanomaterials have been gradually introduced into the research of plugging agents due to their unique physical and chemical properties. Nanomaterials have high specific surface area and excellent mechanical properties, which can significantly improve the overall performance of plugging agents. In addition, organosilicon crosslinkers have become a potential alternative to traditional organometallic crosslinkers due to their excellent thermal and chemical stability.

[0005] Based on this, the present invention proposes a new type of gel plugging agent. By introducing an organic silicon cross-linking agent and nano-alumina, the composition and preparation method of the plugging agent are optimized, so that it can show better performance under high temperature and high pressure environment. At the same time, by adjusting the proportion of each component, the stability and plugging effect of the plugging agent are further improved. The present invention is not only innovative in material selection, but also optimized in preparation process, and has broad application prospects. Summary of the invention

[0006] The purpose of the present invention is to provide a gel plugging agent with a technical idea different from that of the prior art. The plugging agent has a delayed cross-linking effect by introducing an organic silicon cross-linking agent and nano-alumina, and can solve the problem of well leakage in high-temperature deep fractured leakage formations. At the same time, a preparation method of the plugging agent and its application in oil well plugging are provided.

[0007] In order to solve the shortcomings of the above technical problems, the technical scheme adopted by the present invention is: a gel plugging agent, which comprises, by weight percentage, 0.5-4% of partially hydrolyzed polyacrylamide, 1-4% of chitosan, 0.05-0.5% of sodium tripolyphosphate, 0.05-3% of an organosilicon crosslinking agent, 0.1-0.3% of a dispersant, 1-3% of a toughening agent, 1-2% of nano alumina and the remainder of water.

[0008] As a further optimization of the gel plugging agent of the present invention: the gel plugging agent includes, by weight percentage, 3% of partially hydrolyzed polyacrylamide, 2% of chitosan, 0.2% of sodium tripolyphosphate, 2% of organic silicon crosslinking agent, 0.2% of dispersant, 2% of toughening agent, 1% of nano alumina and 89.6% of water.

[0009] As a further optimization of the gel plugging agent of the present invention: the molecular weight of the partially hydrolyzed polyacrylamide is 25-35 million, and the hydrolysis degree of the partially hydrolyzed polyacrylamide is 20-30%.

[0010] As a further optimization of the gel plugging agent of the present invention: the organosilicon cross-linking agent is one or any mixture of organosilane, methyltrimethoxysilane or ethyltriethoxysilane.

[0011] As a further optimization of the gel plugging agent of the present invention: the organosilicon cross-linking agent is methyltrimethoxysilane.

[0012] As a further optimization of the gel plugging agent of the present invention: the dispersant is a mixed dispersant with a mass ratio of organic dispersant to inorganic dispersant of 2-8:1.

[0013] As a further optimization of the gel plugging agent of the present invention: the organic dispersant is polyvinyl alcohol or hydroxypropyl methylcellulose, and the inorganic dispersant is calcium carbonate or nano silicon dioxide.

[0014] As a further optimization of the gel plugging agent of the present invention: the toughening agent is a mixture of nano silicon dioxide and polypropylene fiber in a mass ratio of 1-2:1.

[0015] As a further optimization of the gel plugging agent of the present invention: the particle size of the nano alumina is 10-50 nanometers.

[0016] The present invention also provides a method for preparing a gel plugging agent, comprising the following steps:

[0017] 1. Disperse the toughening agent and nano-alumina in water to obtain a toughening dispersion;

[0018] 2. Dispersing partially hydrolyzed polyacrylamide, sodium tripolyphosphate, chitosan and a dispersant into a toughening dispersion to obtain a polymer dispersion;

[0019] 3. Add the organosilicon cross-linking agent into the polymer dispersion, mix them evenly, and prepare the gel plugging agent.

[0020] The gel plugging agent of the present invention is suitable for plugging leaks in high-temperature and high-pressure environments such as oil wells, can effectively solve the problem of wellbore leakage, and improve the safety and economy of oil and gas field development.

[0021] The present invention has the following beneficial effects: Nano-alumina and organosilicon crosslinking agent are added to the plugging agent of the present invention, and the introduction of these materials improves the mechanical strength and thermal stability of the plugging agent. At the same time, the high specific surface area and unique physical and chemical properties of nano-alumina further enhance the overall performance of the plugging agent. The organosilicon crosslinking agent has excellent chemical stability and can maintain the performance of the gel in a high-temperature environment. By optimizing the proportion of each component and the preparation process, the gel plugging agent of the present invention exhibits more excellent performance in high-temperature deep fractured leakage formations and achieves a better plugging effect. DETAILED DESCRIPTION

[0022] In order to better understand the present invention, the content of the present invention is further explained below in conjunction with embodiments, but the content of the present invention is not limited to the following embodiments.

[0023] <Example 1>

[0024] A gel plugging agent comprises, by weight percentage, 3% of partially hydrolyzed polyacrylamide, 2% of chitosan, 0.3% of sodium tripolyphosphate, 1% of organic silane, 0.2% of dispersant, 2% of toughening agent, 1% of nano aluminum oxide and 90.5% of water.

[0025] The molecular weight of the partially hydrolyzed polyacrylamide is 30-35 million, and the degree of hydrolysis is 25%. The organic silane is methyltrimethoxysilane.

[0026] Wherein, the dispersant is a mixture of polyvinyl alcohol and nano-silicon dioxide in a mass ratio of 3:1.

[0027] The toughening agent is a mixture of nano-silicon dioxide and polypropylene fiber in a mass ratio of 1:1.

[0028] The gel plugging agent is prepared by the following method:

[0029] 1) Dispersing the toughening agent (nano silicon dioxide and polypropylene fiber, mass ratio 1:1) and nano alumina in water to obtain a toughening dispersion;

[0030] 2) dispersing partially hydrolyzed polyacrylamide, sodium tripolyphosphate, chitosan and dispersant (polyvinyl alcohol and nano-silicon dioxide, mass ratio 3:1) into the toughening dispersion to obtain a polymer dispersion;

[0031] 3) Add methyltrimethoxysilane into the polymer dispersion and mix them evenly to obtain a gel plugging agent.

[0032] <Example 2>

[0033] A gel plugging agent comprises, by weight percentage, 2% of partially hydrolyzed polyacrylamide, 3% of chitosan, 0.2% of sodium tripolyphosphate, 1% of organic silane, 0.3% of dispersant, 3% of toughening agent, 2% of nano aluminum oxide and 87.3% of water.

[0034] The molecular weight of the partially hydrolyzed polyacrylamide is 28 million to 32 million, and the degree of hydrolysis is 28%. The organic silane is ethyl triethoxy silane.

[0035] Wherein, the dispersant is a mixture of polyvinyl alcohol and nano-silicon dioxide in a mass ratio of 2:1.

[0036] The toughening agent is a mixture of nano-silicon dioxide and polypropylene fiber in a mass ratio of 1:2.

[0037] The gel plugging agent is prepared by the following method:

[0038] 1) Dispersing a toughening agent (nano silicon dioxide and polypropylene fiber, mass ratio 1:2) and nano alumina in water to obtain a toughening dispersion;

[0039] 2) dispersing partially hydrolyzed polyacrylamide, sodium tripolyphosphate, chitosan and dispersant (polyvinyl alcohol and nano-silicon dioxide, mass ratio 2:1) into the toughening dispersion to obtain a polymer dispersion;

[0040] 3) Add ethyltriethoxysilane into the polymer dispersion and mix them evenly to obtain a gel plugging agent.

[0041] <Example 3>

[0042] A gel plugging agent comprises, by weight percentage, 1% of partially hydrolyzed polyacrylamide, 1% of chitosan, 0.5% of sodium tripolyphosphate, 1.5% of organic silane, 0.1% of dispersant, 2.5% of toughening agent, 1% of nano aluminum oxide and 92.4% of water.

[0043] The molecular weight of the partially hydrolyzed polyacrylamide is 27-32 million, and the degree of hydrolysis is 22%. The organic silane is methyltrimethoxysilane.

[0044] Wherein, the dispersant is a mixture of polyvinyl alcohol and calcium carbonate in a mass ratio of 5:1.

[0045] The toughening agent is a mixture of nano-silicon dioxide and polypropylene fiber in a mass ratio of 1:3.

[0046] The gel plugging agent is prepared by the following method:

[0047] 1) Dispersing a toughening agent (nano silicon dioxide and polypropylene fiber, mass ratio 1:3) and nano alumina in water to obtain a toughening dispersion;

[0048] 2) dispersing partially hydrolyzed polyacrylamide, sodium tripolyphosphate, chitosan and a dispersant (polyvinyl alcohol and calcium carbonate, mass ratio 5:1) into a toughening dispersion to obtain a polymer dispersion;

[0049] 3) Add methyltrimethoxysilane into the polymer dispersion and mix them evenly to obtain a gel plugging agent.

[0050] <Example 4>

[0051] A gel plugging agent comprises, by weight percentage, 2.5% of partially hydrolyzed polyacrylamide, 2% of chitosan, 0.4% of sodium tripolyphosphate, 0.5% of organic silane, 0.3% of dispersant, 1.5% of toughening agent, 1.5% of nano aluminum oxide and 91.3% of water.

[0052] The molecular weight of the partially hydrolyzed polyacrylamide is 30-35 million, and the degree of hydrolysis is 25%. The organic silane is methyltrimethoxysilane.

[0053] Wherein, the dispersant is a mixture of polyvinyl alcohol and nano-silicon dioxide in a mass ratio of 4:1.

[0054] The toughening agent is a mixture of nano-silicon dioxide and polypropylene fiber in a mass ratio of 2:1.

[0055] The gel plugging agent is prepared by the following method:

[0056] 1) Dispersing a toughening agent (nano silicon dioxide and polypropylene fiber, mass ratio 2:1) and nano alumina in water to obtain a toughening dispersion;

[0057] 2) dispersing partially hydrolyzed polyacrylamide, barium tripolyphosphate, chitosan and dispersant (polyvinyl alcohol and nano-silicon dioxide, mass ratio 4:1) into the toughening dispersion to obtain a polymer dispersion;

[0058] 3) Add methyltrimethoxysilane into the polymer dispersion and mix them evenly to obtain a gel plugging agent.

[0059] <Example 5>

[0060] A gel plugging agent comprises, by weight percentage, 3.5% of partially hydrolyzed polyacrylamide, 3% of chitosan, 0.1% of sodium tripolyphosphate, 2% of organic silane, 0.2% of dispersant, 3% of toughening agent, 1% of nano aluminum oxide and 87.2% of water.

[0061] The molecular weight of the partially hydrolyzed polyacrylamide is 29 million to 34 million, and the degree of hydrolysis is 28%. The organic silane is ethyl triethoxy silane.

[0062] Wherein, the dispersant is a mixture of polyvinyl alcohol and calcium carbonate in a mass ratio of 6:1.

[0063] The toughening agent is a mixture of nano-silicon dioxide and polypropylene fiber in a mass ratio of 1:1.

[0064] The gel plugging agent is prepared by the following method:

[0065] 1) Dispersing the toughening agent (nano silicon dioxide and polypropylene fiber, mass ratio 1:1) and nano alumina in water to obtain a toughening dispersion;

[0066] 2) dispersing partially hydrolyzed polyacrylamide, sodium tripolyphosphate, chitosan and a dispersant (polyvinyl alcohol and calcium carbonate, mass ratio 6:1) into a toughening dispersion to obtain a polymer dispersion;

[0067] 3) Add ethyltriethoxysilane into the polymer dispersion and mix them evenly to obtain a gel plugging agent.

[0068] <Comparative Example 1>

[0069] A gel plugging agent comprises, by weight percentage, 2% of partially hydrolyzed polyacrylamide, 2% of chitosan, 0.5% of sodium tripolyphosphate, 2% of chromium acetate, 0.2% of a dispersant, 2% of a toughening agent and 91.3% of water.

[0070] The molecular weight of the partially hydrolyzed polyacrylamide is 20-30 million, and the degree of hydrolysis is 30%.

[0071] Wherein, the dispersant is a mixture of polyvinyl alcohol and calcium carbonate in a mass ratio of 5:1.

[0072] The toughening agent is a mixture of nano-silicon dioxide and polypropylene fiber in a mass ratio of 1:1.

[0073] The gel plugging agent is prepared by the following method:

[0074] 1) Dispersing the toughening agent (nano-silicon dioxide and polypropylene fiber, mass ratio 1:1) in water to obtain a toughening dispersion;

[0075] 2) dispersing partially hydrolyzed polyacrylamide, sodium tripolyphosphate, chitosan and a dispersant (polyvinyl alcohol and calcium carbonate, mass ratio 5:1) into a toughening dispersion to obtain a polymer dispersion;

[0076] 3) Add chromium acetate into the polymer dispersion and mix them evenly to prepare a gel plugging agent.

[0077] <Comparative Example 2>

[0078] A gel plugging agent comprises, by weight percentage, 1.5% of partially hydrolyzed polyacrylamide, 1% of chitosan, 0.2% of diammonium hydrogen phosphate, 1% of chromium propionate, 0.5% of a dispersant, 1.5% of a toughening agent and 94.3% of water.

[0079] The molecular weight of the partially hydrolyzed polyacrylamide is 25-30 million, and the degree of hydrolysis is 25%.

[0080] Wherein, the dispersant is a mixture of polyvinyl alcohol and calcium carbonate in a mass ratio of 4:1.

[0081] The toughening agent is a mixture of nano-silicon dioxide and polypropylene fiber in a mass ratio of 2:1.

[0082] The gel plugging agent is prepared by the following method:

[0083] 1) Dispersing the toughening agent (nano-silicon dioxide and polypropylene fiber, mass ratio 2:1) in water to obtain a toughening dispersion;

[0084] 2) dispersing partially hydrolyzed polyacrylamide, diammonium hydrogen phosphate, chitosan and a dispersant (polyvinyl alcohol and calcium carbonate, mass ratio 4:1) into a toughening dispersion to obtain a polymer dispersion;

[0085] 3) Add chromium propionate into the polymer dispersion and mix them evenly to obtain a gel plugging agent.

[0086] <Leakage plugging performance test>

[0087] In order to evaluate the performance of the gel plugging agent, a set of plugging performance test schemes were designed. The test scheme includes the following steps:

[0088] 1) Prepare samples: Take the gel plugging agent prepared in Example 1-5 and Comparative Example 1-2, add it into the drilling fluid base slurry (4% bentonite slurry), and set it aside after it is completely swollen.

[0089] 2) Experimental device: Use simulated well leakage experimental device to set high temperature and high pressure conditions to simulate the deep fracture leakage formation environment.

[0090] 3) The plugging performance test includes: testing the delayed cross-linking time of the plugging agent, testing the stability of the plugging agent under high temperature conditions, testing the expansion of the plugging agent, and testing the leakage amount of the plugging agent.

[0091] The specific experimental methods are as follows:

[0092] 1) Delayed cross-linking time test: Inject the plugging agent into a simulated well leakage device and observe the gelling time of the plugging agent at room temperature.

[0093] 2) High temperature stability test: Place the plugging agent at high temperature (150°C) for 24 hours to observe the morphological changes and structural stability of the plugging agent.

[0094] 3) Expansion test: After placing the plugging agent at high temperature (150°C) for 24 hours, measure its volume change.

[0095] 4) Loss test: In a simulated well leakage device, the plugging agent is injected into a fractured formation under high temperature and high pressure (150°C, 5MPa) conditions to measure the loss of the plugging agent.

[0096] The summary of the experimental results is shown in Table 1.

[0097] Table 1 Summary of experimental results

[0098]

[0099] It can be seen from the above table:

[0100] 1) Delayed cross-linking time: The synergistic effect of partially hydrolyzed polyacrylamide (HPAM) and nano-chitosan delays the gelation time. HPAM has negatively charged carboxyl groups, while nano-chitosan has positive charges. Chitosan is adsorbed on the main chain of HPAM, hiding the active groups, thereby delaying the occurrence of the cross-linking reaction.

[0101] The ratio and quality of HPAM and nano-chitosan in the embodiment are properly controlled, so that the delayed cross-linking time is between 45-55 minutes, which meets the requirements of high-temperature deep fracture leakage formation. However, due to the lack of nano-chitosan or other regulating components, the cross-linking reaction in the comparative example is too fast, which is not conducive to deep leakage plugging.

[0102] 2) High temperature stability: Cross-linking agents (such as chromium acetate and chromium propionate) provide a stable cross-linking structure under high temperature conditions, enhancing the thermal stability of the gel.

[0103] The organic metal crosslinking agent in the embodiment can still remain stable under high temperature conditions, ensuring that the gel does not decompose or degrade in a high temperature deep environment. However, the crosslinking agent in the comparative example is improperly selected, resulting in an unstable structure at high temperature and poor plugging effect.

[0104] 3) Expansion: The addition of toughening agents (nano-silicon dioxide and polypropylene fibers) significantly improves the expansion performance of the plugging agent. Nano-silicon dioxide has a high specific surface area, can absorb a large amount of water, and has good expansion; polypropylene fibers provide additional structural support to prevent gel shrinkage.

[0105] The proportion of toughening agent in the embodiment is reasonable, so that the plugging agent has significant expansion at high temperature and can effectively fill the crack space. However, the content of toughening agent in the comparative example is low or the proportion is inappropriate, resulting in insufficient expansion and failure to effectively plug the leak.

[0106] 4) Loss: The presence of dispersants (such as polyvinyl alcohol and calcium carbonate) ensures the uniform dispersion of the components in the plugging agent and improves the overall performance. Polyvinyl alcohol enhances the bonding force and calcium carbonate increases the filling effect.

[0107] The dispersant selection and ratio optimization in the embodiment make the plugging agent have low leakage under high temperature and high pressure conditions and excellent plugging effect. The comparison example has large leakage and poor plugging effect due to improper dispersant selection or unreasonable ratio.

[0108] By analyzing the effects of various chemical agents on the performance of plugging agents, the following conclusions can be drawn:

[0109] 1) The introduction of nano-chitosan effectively prolongs the gelling time of the plugging agent, ensuring that the plugging agent can reach the deep cracks and then gel.

[0110] 2) The use of organic metal cross-linking agents (such as chromium acetate and chromium propionate) significantly improves the stability of the plugging agent under high temperature conditions, ensuring its long-term effectiveness in high-temperature deep environments.

[0111] 3) The reasonable ratio of toughening agent (nano-silica and polypropylene fiber) improves the expansion performance of the plugging agent, ensuring that it can fully fill the cracks and achieve effective plugging.

[0112] 4) The selection and ratio optimization of dispersants (polyvinyl alcohol and calcium carbonate) improve the uniform dispersion and overall performance of the plugging agent components, reduce the loss and enhance the plugging effect.

[0113] Due to these optimized formula designs and reasonable agent selection, the gel plugging agent of the embodiment exhibits excellent plugging performance in high-temperature deep fractured leakage formations, which is significantly better than the product of the comparative example.

[0114] The above describes the specific embodiments of the present invention. It should be understood that the present invention is not limited to the above specific embodiments, and those skilled in the art may make various modifications or variations within the scope of the claims, which do not affect the essence of the present invention.

Claims

1. A gel plugging agent containing an organosilicon crosslinking agent and nano-alumina and a preparation method thereof, characterized in that: Calculated by weight percentage, it includes 0.5-4% of partially hydrolyzed polyacrylamide, 1-4% of chitosan, 0.05-0.5% of sodium tripolyphosphate, 0.05-3% of organic silicon crosslinking agent, 0.1-0.3% of dispersant, 1-3% of toughening agent, 1-2% of nano aluminum oxide and the balance of water.

2. The gel plugging agent as claimed in claim 1, characterized in that: Calculated by weight percentage, it includes 3% of partially hydrolyzed polyacrylamide, 2% of chitosan, 0.2% of sodium tripolyphosphate, 2% of organic silicon crosslinking agent, 0.2% of dispersant, 2% of toughening agent, 1% of nano alumina and 89.6% of water.

3. The gel plugging agent according to claim 1 or 2, characterized in that: The molecular weight of the partially hydrolyzed polyacrylamide is 25-35 million, and the hydrolysis degree of the partially hydrolyzed polyacrylamide is 20-30%.

4. The gel plugging agent according to claim 1 or 2, characterized in that: The organosilicon crosslinking agent is one or any mixture of organosilane, methyltrimethoxysilane or ethyltriethoxysilane.

5. The gel plugging agent as claimed in claim 4, characterized in that: The organosilicon crosslinking agent is methyltrimethoxysilane.

6. The gel plugging agent according to claim 1 or 2, characterized in that: The dispersant is a mixed dispersant with a mass ratio of an organic dispersant to an inorganic dispersant of 2-8:

1.

7. The gel plugging agent as claimed in claim 6, characterized in that: The organic dispersant is polyvinyl alcohol or hydroxypropyl methylcellulose, and the inorganic dispersant is calcium carbonate or nano silicon dioxide.

8. The gel plugging agent as claimed in claim 1, characterized in that: The toughening agent is a mixture of nano silicon dioxide and polypropylene fiber in a mass ratio of 1-2:

1.

9. The gel plugging agent as claimed in claim 1, characterized in that: The particle size of the nano-alumina is 10-50 nanometers; 1) A method for preparing the gel plugging agent as claimed in claim 1, characterized in that it comprises the following steps: 2) dispersing the toughening agent and nano-alumina in water to obtain a toughening dispersion; 3) dispersing partially hydrolyzed polyacrylamide, sodium tripolyphosphate, chitosan and a dispersant into a toughening dispersion to obtain a polymer dispersion; 4) adding an organosilicon cross-linking agent into the polymer dispersion and mixing them evenly to obtain a gel plugging agent.

10. Use of the gel plugging agent according to any one of claims 1 to 9 or the gel plugging agent prepared by the preparation method according to claim 10 in plugging oil wells.

Citation Information

Patent Citations

  • Temperature-controllable gel plugging agent as well as preparation method and application thereof

    CN112980407A

  • Gel plugging agent as well as preparation method and application thereof

    CN116023914A

  • Temporary plugging type gel plugging agent as well as preparation method and application thereof

    CN118056882A

  • High-temperature-resistant reinforced gel drilling plugging agent and preparation method thereof

    CN118064116A